2022
DOI: 10.11591/ijece.v12i2.pp1683-1694
|View full text |Cite
|
Sign up to set email alerts
|

Bandwidth enhancement of dual-band bi-directional microstrip antenna using complementary split ring resonator with defected structure for 3/5 GHz applications

Abstract: <span>This paper presents a bandwidth enhancement of a dual-band bi-directional rectangular microstrip patch antenna. The novelty of this work lies in the modification of conventional rectangular microstip patch antenna by using the combination of two techniques: a complementary split ring resonator (CSRR) and a defected patch structure (DPS). The structure of antenna was studied and investigated via computer </span><span>simulation technology (CST). The dimension and position of CSRR on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…As a result of this comparison, a considerable improvement in the antenna gain is discovered, along with an acceptable size reduction. 3.5 GHz 1.88 [11] 3.5 GHz 5.3 [16] 3.6 GHz 2.52 [18] 3.5 GHz 4.2 [28] 3.5 GHz 4.57 4.90 5 [31] 3.5 GHz 6.05 [34] 3.5 GHz 5.43 [35] 3.29 GHz 3.38 [36] 3.36 GHz 1.07 [37] 3.5 GHz 5.8 [38] 3.45 GHz 3.83 [40] 3.5 GHz 4.28 [41] 3.45 GHz 4.64 [42] 3.5 GHz 3.338 4.66 5.08 This work 3.5 GHz 6.02 6. CONCLUSION A 3.5 GHz microstrip patch antenna has been designed in the said paper.…”
Section: Results Analysismentioning
confidence: 99%
“…As a result of this comparison, a considerable improvement in the antenna gain is discovered, along with an acceptable size reduction. 3.5 GHz 1.88 [11] 3.5 GHz 5.3 [16] 3.6 GHz 2.52 [18] 3.5 GHz 4.2 [28] 3.5 GHz 4.57 4.90 5 [31] 3.5 GHz 6.05 [34] 3.5 GHz 5.43 [35] 3.29 GHz 3.38 [36] 3.36 GHz 1.07 [37] 3.5 GHz 5.8 [38] 3.45 GHz 3.83 [40] 3.5 GHz 4.28 [41] 3.45 GHz 4.64 [42] 3.5 GHz 3.338 4.66 5.08 This work 3.5 GHz 6.02 6. CONCLUSION A 3.5 GHz microstrip patch antenna has been designed in the said paper.…”
Section: Results Analysismentioning
confidence: 99%
“…The progression of research works on the DGSs in RF and microwave for the last 10 years have shown evidences of improvement towards design realizations and performances. DGS has several advantages on the circuit [12], unwanted frequency suppression [13]- [15], bandwidth enhancement of antennas [16], [17], size compactness [18], [19], high power handling capability [20], isolation in antenna designs [21]- [23], and compensating parasitic capacitance of switching element to improve isolation [24], [25].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many techniques were applied to improve the impedance bandwidth with patch antennas such as believed half-cut structure [7], p-in diode switching [8], Sierpinski carpet fractal monopole antenna (SCFMA) [9] and also by using double stub matching with proximity coupled feed [10]. Some researchers use two techniques such as a [11]. Moreover, by using Substrate Removal may easily enhance the bandwidth and efficiency [12].…”
Section: Introductionmentioning
confidence: 99%